2018
DOI: 10.1136/annrheumdis-2018-213289
|View full text |Cite
|
Sign up to set email alerts
|

Inequity in access to bDMARD care and how it influences disease outcomes across countries worldwide: results from the METEOR-registry

Abstract: ObjectiveTo establish in a global setting the relationships between countries’ socioeconomic status (SES), measured biological disease modifying antirheumatic drug (bDMARD)-usage and disease outcomes. To assess if prescription and reimbursement rules and generic access to medication relates to a countries’ bDMARD-usage.MethodsData on disease activity and drug use from countries that had contributed at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 17 publications
(5 reference statements)
4
55
0
Order By: Relevance
“…So when making therapeutic decisions, drugs that are less costly must be preferred over more costly ones, as long as they are similarly efficacious and safe and in line with the therapeutic paradigms 20. As mentioned in the introduction, in many countries, the high costs of treatment limit the availability of modern therapies (inequity),14 the availability of biosimilars can address this and provide significant reductions of healthcare budgets, when their price is sufficiently low and their application is then reinforced by payers or politicians 16 62. The task force voted unanimously to place this item as the last overarching principle, without a change in wording.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So when making therapeutic decisions, drugs that are less costly must be preferred over more costly ones, as long as they are similarly efficacious and safe and in line with the therapeutic paradigms 20. As mentioned in the introduction, in many countries, the high costs of treatment limit the availability of modern therapies (inequity),14 the availability of biosimilars can address this and provide significant reductions of healthcare budgets, when their price is sufficiently low and their application is then reinforced by payers or politicians 16 62. The task force voted unanimously to place this item as the last overarching principle, without a change in wording.…”
Section: Resultsmentioning
confidence: 99%
“…The increasing number of effective drugs and modes of action (MOAs) has improved the likelihood of reaching the treatment target for individuals with RA, but high drug-costs still limit widespread use and thus contribute to inequity of access to best care across various regions and countries 13–15. The approval and advent of biosimilar (bs) DMARDs has introduced price competition and led to a considerable reduction of the net costs of biological (b) DMARDs,16 although this may not be true in all countries and may require further exploration.…”
mentioning
confidence: 99%
“…Current guidelines recommend access to biologics based on disease duration, disease severity, and number of insufficient responses to conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) [69][70][71][72][73][74][75][76], although differences in expert opinion may lead to divergent interpretations of the same evidence between guidelines. In addition, high costs and poor affordability often restrict patient access to biologics [77][78][79][80][81], alongside factors such as prescription controls and limitations in access to healthcare services [81]. Furthermore, national reimbursement criteria can be more restrictive than treatment guidelines, leading to disparities in patient access to biologics among countries [77,82].…”
Section: Key Pointsmentioning
confidence: 99%
“…In addition, high costs and poor affordability often restrict patient access to biologics [77][78][79][80][81], alongside factors such as prescription controls and limitations in access to healthcare services [81]. Furthermore, national reimbursement criteria can be more restrictive than treatment guidelines, leading to disparities in patient access to biologics among countries [77,82]. For example, a recent study in the European region (defined as 37 European countries, plus Russia and Turkey) found that only 59% of patients eligible for biologics according to EULAR guidelines (DAS28 > 3.2 and ≥ 2 csDMARD treatment failures) remained eligible following application of national reimbursement criteria [79].…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation